Batas Militar [videorecording] a documentary on Martial law in the Philippines - Apostol, Eugenia; Arroyo, Fely.; Magsanoc, Kara.; Tiongson, Lito.; Foundation for Worldwide People Power (Philippines). (Pasig City The Foundation, 1997)
A documentary on Martial law in the Philippines.
VHS.
Credits : Narrator, Joonee Gamboa.
Keywords: Marcos, Ferdinand Edralin -- 1917-1989.; Martial law -- Philippines; Feature films; Philippines -- Politics and government -- 1972-1981.